(untitled) (Revista de Ciências Agroveterinárias, 2018)
One of the main factors related to the quality of edible vegetable seedlings is the type of substrate used. The growth variables of cucumber seedlings grown on alternative substrates to the commercial substrate, having increasing levels of coffee drying residues (chaff). The experiment was conducted under a completely randomized design with six treatments and ten replications, where: T1: commercial substrate (CS); T2: 0% chaff (CH) + 40% carbonized rice husk (CRH) + 15% coconut fiber (CF) + 5% eggshell (ES) + 40% CS; T3: 10% CH + 40% CRH + 15% CF + 5% ES + 30% CS; T4: 20% CH + 40% CRH + 15% CF + 5% ES + 20% CS; T5: 30% CH + 40% CRH + 15% CF + 5% ES + 10% CS; T6: 40% CH + 40% CRH + 15% CF + 5% ES + 0% CS. The variables evaluated were electrical conductivity of substrates, dry mass of the root system and the aerial part, seedling height, stem diameter and number of leaves. Increasing proportions of chaff also increase the electrical conductivity of the substrate. Proportions around 15 to 20% of chaff in the composition of the substrate present the highest values of stem diameter, dry mass of the root system and of the aerial part. Proportions up to 30% of the substrate constituted by 40% rice husk, 15% coconut fiber, 5% egg husk and 10% commercial substrate can also be used without loss in the growth variables of cucumber seedlings.